2020
DOI: 10.3390/molecules25235571
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Murine SUMO Proteome in Response to Cardiac Ischemia and Reperfusion Injury

Abstract: SUMOylation is a reversible posttranslational modification pathway catalyzing the conjugation of small ubiquitin-related modifier (SUMO) proteins to lysine residues of distinct target proteins. SUMOylation modifies a wide variety of cellular regulators thereby affecting a multitude of key processes in a highly dynamic manner. The SUMOylation pathway displays a hallmark in cellular stress-adaption, such as heat or redox stress. It has been proposed that enhanced cellular SUMOylation protects the brain during is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…To identify the potential target proteins of SUMOylation in the mouse heart with cardiac I/R, an unbiased proteomic analysis was conducted. There were 102 proteins that significantly interacted with SUMO1, including the composition of the SUMO mechanism and the ubiquitin proteasome system [ 143 , 144 ], multiple subunits of 20S proteasome core particle, and metabolic enzymes involved in glycolytic and oxidative metabolic pathways [ 145 ]. High molecular weight SUMO1 conjugates were significantly reduced 24 h after reperfusion.…”
Section: Sumoylation Of Proteins and Cvdmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the potential target proteins of SUMOylation in the mouse heart with cardiac I/R, an unbiased proteomic analysis was conducted. There were 102 proteins that significantly interacted with SUMO1, including the composition of the SUMO mechanism and the ubiquitin proteasome system [ 143 , 144 ], multiple subunits of 20S proteasome core particle, and metabolic enzymes involved in glycolytic and oxidative metabolic pathways [ 145 ]. High molecular weight SUMO1 conjugates were significantly reduced 24 h after reperfusion.…”
Section: Sumoylation Of Proteins and Cvdmentioning
confidence: 99%
“…Further, 55 proteins were found to be potential SUMO2/3 target proteins, including ubiquitin and proteasome subunits, gene expression regulators and transcription factors, RNA binding proteins and splicing regulators, heat shock proteins, and specific proteins that play important roles in cardiac function. Myocardial ischemia decreased the SUMO level of the whole protein and the number and catalytic activity of de-SUMO enzymes [ 145 ]. The heart SUMO2 target protein undergoes a dynamic adaptation process in cardiac I/R.…”
Section: Sumoylation Of Proteins and Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that the dynamics of the SUMOylation/deSUMOylation was altered during MI/R injury correlating with the decrease in SENPs activities, especially that of SENP3 ( 54 ). Presumably, the SUMOylation system may control the response of the heart to hypoxic/ischemic stress ( 55 ). Nevertheless, little is known about the regulation of the SUMOylation system and the potential target proteins during MI.…”
Section: Process Of Protein Sumoylationmentioning
confidence: 99%
“…Human desumoylation proteases SENPs, including SENP1, SENP 2, SENP 3, SENP 5, SENP 6 and SENP 7, play a key role in this pathway ( 19 ). One is to catalyze the transformation of SUMO precursor into its active form; the other is to cut off the isopeptide bond between SUMO and the target protein to realize desumoylation ( 20 ). SENP is involved in the regulation of the cell cycle, cell proliferation, oxidative stress signaling or tumor gene fusion, leading to tumor formation.…”
Section: Introductionmentioning
confidence: 99%